Proposed assessment framework based on bloom taxonomy cognitive competency: Introduction to programming - Lajis, Adidah; Mohamad Nasir, Haidawati; Abdul Aziz, Normaziah (Association for Computing Machinery, 2018)
Programming is a difficult course and often the result of its assessment is not encouraging. Programming skill is very important to graduate in order to get job and to success in the industry. A careful assessment is required to help the student learning. It is proved that the assessment itself will improve the learning. The review showed to-date that there are several automatic assessment for programming skills, however, there is no common grading being applied. This paper, is proposing an assessment framework based on Bloom Taxonomy cognitive domain to assess students programming skills. The focus is on basic programming course which introduce the programming concept to students.